Древний Египет: энциклопедия (Энциклопедия для умников и умниц, 2012)
Экземпляры: Подгорновская с/б (20131123) / Инвентарный номер: 39637 / Цена: 80.52р. / Сис.шифр: 63.3(6) я 2 / Авт.знак: Д 73 / ГРНТИ: 03.91 / ББК: 63.3(6) я 2